Optimal location and sizing of storage units in a drainage system. (September 2016) - Cunha, Maria C.; Zeferino, João A.; Simões, Nuno E.; Saldarriaga, Juan G.
Abstract: Adapting urban stormwater drainage systems is essential to handling increased urbanization and climate change. Within an urban area, storage units are an efficient solution to reduce peak runoff, but their implementation involves complex decisions. This paper presents a novel optimization model for defining, in existing sewer drainage systems, the number of storage units, their location, size and the orifice dimensions. The orifice is used to reduce storage unit outflow regulating downstream flows. These components allow an integrated flow control and flooding reduction throughout the network. The desired solution should offer the lowest cost and try to avoid any major flooding impact. The model includes hydraulic, flood and capacity constraints and it is solved through a simulated annealing algorithm that calls upon a dynamic rainfall-runoff simulator for complete evaluation of each solution. The performance of the optimization model is assessed through a case study inspired by a real urban sewer network. Highlights: A novel optimization model for location and sizing of storage units is proposed. Orifices are optimized to regulate the outflow from the storage units. The model aims to avoid flood throughout the entire network at a minimum expense. A simulated annealing algorithm is designed to solve the model. SWMM is used to evaluate the effects of each rainfall event on the drainage system.